Perceptions of premium service and superiority: Why do customers pay more for high-value-added domestic airline services in Japan?. (October 2016) - Osaki, Takanori; Kubota, Yukihiko
Abstract: This paper clarifies the factors influencing customers' perceptions of premium service and superiority for high-value-added domestic airline services in Japan, and explains how these perceptions impact customer loyalty. To gather data for the analysis of consumers' perceptions, a questionnaire survey of 515 respondents who use high-value-added domestic airline services was conducted. These respondents' data were analyzed using structural equation modeling. The most valuable finding is the distinction between the perceptions of premium service and superiority, both of which strongly influence customer loyalty. This finding has two important implications. First, staff correspondence has a strong influence on customer loyalty – not directly, but through customers' perceptions of premium service and superiority. Second, perceptions of premium service and superiority influence customer loyalty separately. This finding may assist in the development of innovative high-value-added services. Highlights: Customer loyalty is explored via the case study of high-value-added domestic airline services in Japan. To understand the factors of customer loyalty, customers' perceptions of premium service and superiority are focused on. The distinction between the perceptions of premium service and superiority is clarified. Staff correspondence has a strong influence on customer loyalty through the perceptions of premium service and superiority. Perceptions of premium service and superiority influence customer loyalty separately.